PENGARUH PENGGUNAAN MEDIA ZOOM DAN MINAT BELAJAR TERHADAP TINGKAT PEMAHAMAN MAHASISWA AKUNTANSI - Mira Septiani; Endang Wulandari; Zahra Alfiah Putri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Online learning has become the primary alternative for learning today, with Zoom being one of the most widely used online learning platforms. In the context of accounting students, understanding complex material presents a challenge, especially if it is not supported by a strong interest in learning. This study aims to analyze the effect of Zoom media use and learning interest on the level of understanding of accounting students at private universities in South Jakarta. The population in this study were all active accounting students enrolled at private universities in South Jakarta in the 2025/2026 academic year, and convenience sampling was used for sampling. The quantitative method used in this study was multiple linear regression analysis with the assistance of SPSS Version 26 software. The results showed that partially, the Zoom media variable had no effect on student understanding, while the learning interest variable did. Simultaneously, it was concluded that Zoom media and learning interest together had an effect on student understanding.